If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -1x = 18 Reorder the terms: -1x + 2y = 18 Solving -1x + 2y = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -1x + 2y + -2y = 18 + -2y Combine like terms: 2y + -2y = 0 -1x + 0 = 18 + -2y -1x = 18 + -2y Divide each side by '-1'. x = -18 + 2y Simplifying x = -18 + 2y
| y+7+y+7+2y+2y=3y+4+3y+4+y-1+y-1 | | 2yx-3x=y | | 6(x+3)-2=58 | | 29+-3x=123 | | 9+4x-10=5x | | 4x+40-2x-16=0 | | 2(2-x)=4(x-5) | | (5x+34)+(8x+15)=88 | | X=-.15 | | 5x+8x+10=-42 | | x/12-10=5/24 | | 5x+10-3x+12=6 | | 12+4n=4n+12 | | 5ex-7-15=0 | | (8x+16)+(6x-60)=180 | | 3x+60+2x-10=-5 | | -(n-4)+3=-(n-7) | | 2x=4y-14 | | 8-2(4x+9)=6x-4(x-5) | | -4x+12-22=-10 | | 3x+6x+2=11 | | X+2+5x=2-2x | | -4x+3-22=-10 | | 5x-3=5(x-1)+2 | | 3x+105+4x+56=-28 | | 9x-1=243 | | 0=7w-w^2 | | 44/246 | | 20-p=40 | | 7x^4+x=0 | | 3(7x+4)=6(x+2) | | -8-k=-25 |